Varanasi: myths and scientific studies ; proceedings of an interdisciplinary workshop [Vārānasi 2010] - Jayaswal, Vidula (Aryan Books International, 2013)
Contributed articles presented at one-day Interdisciplinary Workshop on Myths and Scientific Studies held on November 02, 2010 under the auspices of Banaras Hindu University